Commercialization of microcavity plasma devices and arrays: Systems for VUV photolithography and nanopatterning, disinfection of drinking water and air, and biofilm deactivation for medical therapeutics. Issue 10 (17th August 2022) - Kim, Jinhong; Mironov, Andrey E.; Cho, Jin H.; Sievers, Dane S.; Herring, Cyrus M.; Park, Sehyun; Sun, Peter P.; Liang, Zhihu; Chen, Wenyuan; Park, Sung‐Jin; Eden, J. Gary
Abstract: A little more than two decades after the introduction of the first microcavity plasma devices, a growing body of commercial products based on the remarkable properties of these low‐temperature, atmospheric plasmas is now available. Following a brief review of early microplasma lamp development, this article describes microplasma‐based devices and systems currently being manufactured for applications in photolithography, photopatterning, and other nanofabrication processes, such as atomic layer deposition, spectroscopic identification and analysis of materials (including wide bandgap crystals), the disinfection of drinking water in off‐grid communities, deactivating COVID‐19 and other pathogens in air and on surfaces in public spaces, and vacuum ultraviolet lamps for driving atomic clocks. The microplasma‐based treatment of otitis media in the human ear will also be discussed. Abstract : The development of arrays of microcavity plasmas has led to the commercialization of technologies ranging from deep‐ultraviolet and vacuum ultraviolet lamps for photolithography and nanopatterning, as well as atomic clocks, to compact ozone generators for the disinfection of drinking water in remote locations and the identification and analysis of materials such as laboratory‐grown diamonds. Other applications of microplasmas such as the treatment of ear infections are also discussed.